CONCEPT OF «PUBLIC ADMINISTRATION»IN THE DOMESTIC SCIENTIFIC DISCUSSION - Victoria Аndriyash; Alexander Yevtushenko (Публічне управління та регіональний розвиток, 2018)
The formation of Ukraine as a full-fledged competitive partner in the world civilization requires scientific substantiation of the principles of public administration, which can be interpreted as management, carried out on the basis of the will of the community (a collective of people) and implemented by community-defined actors, to meet the needs and achieve the goals of the community as an object of management, which in fact means the functioning and development of the collective of people. The modern system of state and self-government management in Ukraine is undergoing a period of serious modernization due to the evolution of state-political factors of the improvement of mechanisms of social development, which is connected with the formation of a strong state, including all aspects of its development – economic, political, scientific, socio-cultural, and others. That is why the article is devoted to an attempt to analyze the content and essence of the concept of «public management» in the context of the research carried out by domestic scientists and, accordingly, determine the patterns of its formation within the existing scientific traditions, which will serve as the basis for the further formation of a unified scientific and theoretical basis of public administration research in Ukraine. The article reveals the concept of «public management» in the national scientific thought. The main factors that influenced the emergence of such a new form of government in the public sector as public administration were identified. The correlation between the concepts of «public management» and «public administration» is analyzed. Based on the analysis of the scientific views of domestic scientists, it is proved that the concept of «public administration» is not identical with the concept of «state administration», which is widely used in Ukraine. The identification of these concepts leads to a certain confusion in the sense of such phenomenon as «public administration», which is considered inadmissible in the context of the need to form a stable categorical apparatus. It is proved that these concepts should not be used as identical, they require a thorough study in Ukraine and systematization of existing work. The necessity to study the process of formation of public administration in Ukraine, its specificity and the dynamics of the concept change and possible variants of development perspectives with the consideration of all possible trends in the field of management of the public and public sphere is substantiated. The use of the proposed approaches of domestic researchers regarding the notion and content of «public management» as a complex, multi-faceted and ambiguous phenomenon in the public sphere is one of the prerequisites for the formation of a common approach to understanding «public administration» in the context of certain aspects of public administration.